Fabrication of ternary zinc-nickel-copper oxide microsphere nanocomposite photoanode material for boosting dye-sensitized solar cell efficiency - Kandasamy M.; Seikh A.H.; Suresh S.; Kumar A.; Husain A.; Vijayakumar P.; Dele-Afolabi T.T.; Pugazhenthiran N.; Murugesan S.; Ansari M.N.M. (Elsevier Ltd, 2025)
The present study focuses on the development of cost-effective and efficient energy conversion material for fossil-fuel free society. In this context, ternary ZnO-NiO-CuO nanocomposite (NC) prepared using a facile chemical co-precipitation method was used as a photoanode material in dye-sensitized solar cell (DSSC). Concurrently, ZnO nanoparticles (NPs), binary ZnO-NiO and ZnO-CuO NCs were also prepared, characterized and employed as photoanode materials in DSSC. XRD diffraction analysis disclosed successful formation of nanomaterials with relevant structural parameters. SEM investigation displayed spherical and microsphere morphology of ternary ZnO-NiO-CuO NC. EDAX examination confirmed its purity. TEM and HRTEM analysis revealed that the morphology of ternary ZnO-NiO-CuO NC exhibits microspheres with porous nature, whose size ranges from 150 nm to 400 nm. Less intense PL peaks suggested anticipation of relatively low charge recombination, better charge separation and fast electron transport in ternary ZnO-NiO-CuO NC photoanode based DSSC. Consequently, photovoltaic behavior of DSSC integrated with ternary ZnO-NiO-CuO NC photoanode exhibited significantly higher PCE (?) of 4.96 % when compared to DSSC fabricated using pristine ZnO NPs (2.48 %), ZnO-NiO (3.18 %) and ZnO-CuO NC (4.35 %) photoanodes. ? 2024 Elsevier B.V.